A Study on Semantic Web Languages and Technologies (International Journal of Engineering and Computer Science, 2014)
The World Wide Web (WWW) has changed the way people communicate with each other, how information is spread and retrieved. The word semantic web includes techniques that promise to dramatically improve the current WWW and its use. The Semantic web area has seen rapid development in current era with the improvement of technologies every now and then. The Semantic web is propagated by the World Wide Web consortium (W3C), an international standardization body for the web. The main purpose of the Semantic web is to help users locate better, organize and access the information on the web. The language used should be a natural language so that users find it comfortable to deal with any web pages or Applications. This paper gives us the overview of web languages and technologies used now-a-days in present era.